2003
DOI: 10.1381/096089203321136575
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue as a Sealant for High-Risk Anastomosis in Surgery for Morbid Obesity

Abstract: Fibrin sealant may be useful in preventing leaks and promoting healing of the "high risk" anastomosis during complex gastrointestinal surgery. While the cost of fibrin glue is to be considered, re-operation and management of subsequent enterocutanous fistulas or anastomotic strictures may be more costly than routine use for high-risk morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 6 publications
0
54
1
1
Order By: Relevance
“…In a randomized study on esophageal anastomoses in infants born with esophageal atresia, a significantly reduced incidence of anastomotic leakage and stricture was found in the group sealed with FG [85]. Two human studies on FG sealing of anastomoses in patients with Roux-en-Y gastric bypass found a nonsignificantly decreased incidence of anastomotic leakage in the sealing group [86,87]. Another human study on anastomotic leakage after laparoscopic resection of rectal cancer found a leakage rate of 5.8% in the FG-sealed group compared with 10.9% in the nonsealed group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized study on esophageal anastomoses in infants born with esophageal atresia, a significantly reduced incidence of anastomotic leakage and stricture was found in the group sealed with FG [85]. Two human studies on FG sealing of anastomoses in patients with Roux-en-Y gastric bypass found a nonsignificantly decreased incidence of anastomotic leakage in the sealing group [86,87]. Another human study on anastomotic leakage after laparoscopic resection of rectal cancer found a leakage rate of 5.8% in the FG-sealed group compared with 10.9% in the nonsealed group.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many of these attempts have failed to show convincing results [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Numerous studies have reported on the sealing of gastrointestinal anastomoses with fibrin glue (FG), also called fibrin sealant.…”
Section: Introductionmentioning
confidence: 99%
“…Oversewing the staple line [4], the use of fibrin sealants [3,9,17,24], and the application of buttressing material [18,25] have all been evaluated in the literature as possible options to minimize postoperative ASL.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly the use of these products in anastomosing other structures such as vas deferens, nerves, and hollow viscus is well reported in the literature. [52][53][54][55][56][57] However, concerns regarding the inherent thrombogenicity of these products and the potential for triggering intraluminial thrombosis exist. 58 Although promising animal studies have been published, [59][60][61][62][63][64] few clinical series exist.…”
Section: Adhesivesmentioning
confidence: 99%